Identification Of Disparities In Educational Facilities Among Indonesian Provinces Using K-Means Clustering - Putri, Ananda Desilia; Dewi, Harni Selasih; Widodo, Edy (LPPM-ITEBA, 2026)
Education is one of the indicators used to measure a country's progress, due to its important role in producing quality human resources. Good education is certainly supported by the availability of adequate educational facilities. However, Indonesia's diverse geography poses a challenge in terms of equal access to education. Provinces classified as 3T regions face a shortage of educational facilities and teaching staff. This study aims to group provinces in Indonesia based on educational facility indicators for the 2023/2024 academic year using K-Means Clustering Analysis. The data used covers 38 provinces with 18 educational facility indicators, which were analyzed after data pre-processing. The results of this study obtained 3 clusters, where the first cluster consisted of 1 province with poor access and infrastructure conditions, the second cluster consisted of 17 provinces with fairly good access and infrastructure conditions, and the third cluster consisted of 20 provinces with very good access and infrastructure conditions. The clustering results from this study are expected to serve as a reference for the formulation of policies on the equitable distribution of educational facilities and the determination of development priorities in the education sector in Indonesia.